PP-015 Using a closed-system transfer device leads to better control of occupational exposure in routine practice. (24th March 2015) - Simon, N; Vasseur, M; Pinturaud, M; Soichot, M; Richeval, C; Humbert, L; Bonnabry, P; Allorge, D; Décaudin, B; Odou, P
Abstract : Background: Closed-system transfer devices (CSTD) are promoted in all recommendations to reduce the occupational exposure to antineoplastic drugs during the compounding process. Numerous in vitro studies have shown that using the PhaSeal system may limit chemical contamination. Purpose: To compare the chemical contamination inside isolators between a standard (S) and a PhaSeal (P) compounding process in routine practice. Material and methods: A 6-month prospective study started at the opening of a new compounding unit (checked as not contaminated). Two isolators with 2 workstations were used, one to compound with standard devices (needles and spikes) and the other one using the PhaSeal devices. Drugs were alternatively compounded in each isolator (90 preparations/day). Sampling was performed by wiping three surfaces (gloves, window (inner surface), worktop), before and after a cleaning process. Exposure to ten antineoplastic drugs (cyclophosphamide, ifosfamide, dacarbazine, 5-FU, methotrexate, gemcitabine, cytarabine, irinotecan, doxorubicin and ganciclovir) was evaluated on wipes by LCMSMS analysis. Contamination rates (% of samples revealing contamination) were compared using a Chi 2 test and the drug amounts by a Mann-Whitney test. Significance was defined as p < 0.05. Results: 655 samples were analysed (P: n = 327, S: n = 328). The amounts of drugs compounded in each isolator were not significantly different, excepted for methotrexate. The overall contamination rate before cleaning was significantly lower in the PhaSeal isolator (P: 12.6% vs. S: 25.4%; <0.0001). Both isolators were mainly contaminated before cleaning by gemcitabine (P: 295.9 vs. S: 224.7 ng; p < 0.67) and cyclophosphamide (P: 139.7 vs. S: 575.8 ng; p < 0.03). Only traces of methotrexate were retrieved one time in each isolator. Conclusion: This study demonstrates that using a CSTD significantly reduces the overall contamination without cancellation. This intermediate analysis will be implemented by an analysis of the drug amounts handled and the occurrence of incidents. Reference: Sessink PJ, Trahan J, Coyne JW. Reduction in surface contamination with antineoplastic drugs in 22 hospital pharmacies in the US following implementation of a closed-system drug transfer device. Hosp Pharm 2013;48(3):204–12 Conflict of interest